Implementasi Nilai-Nilai Kebangsaan Berbasis UUD 1945 dalam Pengaruh Keamanan Data dan Kemudahan Bertransaksi terhadap Minat Beli Mahasiswa melalui Dompet Digital DANA - Fareel Ardiansyah; Edy Soesanto; Hani Sifana (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
With the development of the digital world, people can now not only use cash as a means of payment, but can also use cash in electronic form through payment applications such as digital wallets which replace the function of cash so that it becomes a more efficient and efficient means of payment. . One type of digital wallet (e-wallet) payment tool that is widely used by people in Indonesia is the DANA application. This research uses a literature review method, namely utilizing literature to obtain field data without direct involvement. Legal protection for the security of personal data is regulated in Article 28 G (1) of the Personal Data Protection Law. This is reiterated in Article 26 of the ITE Law which states that personal data is everyone's personal right. The DANA digital wallet is also protected by Law Number 11 of 2008 concerning Information and Electronic Transactions. The aim of this research is to determine the impact of data security and ease of transactions on students' interest in making purchases via the DANA digital wallet. Based on the findings obtained, security and ease of transactions have a significant influence on students' interest in using DANA, and as the level of security and ease of transactions increases, interest in purchasing through DANA will also increase.